OUTCOMES AND COMPLICATIONS AFTER TRANSRECTAL ULTRASOUND-GUIDED PROSTATE BIOPSY IN 2016-2022 AT HOAN MY CUU LONG HOSPITAL (Vietnam Journal of Community Medicine, 2022)
Objectives: The transrectal ultrasound (TRUS)-guided prostate biopsy protocols have beenan optimizing strategy for diagnosis of prostate cancer. In this study, we aim to examine thecancer detection rate and the complications following prostate biopsy at Hoan My Cuu LongHospital.Methods: We retrospectively reviewed medical data of patients who underwent TRUSguided prostate biopsy in 12/2016 to 08/2022 at our institution. The pathological outcomes,major complications were recorded and assessed clinically.Results: In this study, 129 patients who underwent TRUS-guided prostate biopsy wereenrolled. The mean age was 73,33 years. The complications were infrequent, hematospermiain 13 patients (10.1%). Overall, 40 patients (31%) were diagnosed with prostate cancer.Conclutions: Our study demonstrated the cancer detection rate, and type of complicationsfollowing TRUS-guided prostate biopsy.
Keywords: Prostate cancer, transrectal ultrasound-guided prostate biopsy.